Technology and equipment of vertical‑stack molding for the production of castings without pattern drafts - V. V. Fonov; S. N. Grechanik; D. M. Golub (Литьë и металлургия, 2021)
The article reports on the new technology and equipment of vertical‑stack molding (VSM), created by OJSC “BELNIILIT” for the manufacture of vertical‑stack molds. The development is intended for the production of molds and cast blanks of oil, which are later used for the manufacture of piston rings of internal combustion engines.The difference between the above‑mentioned technology and traditional methods of VSM is the use of models without drafts. The development is export‑oriented and has a great economic effect for ring manufacturers due to the absence of drafts on castings, since part of the mechanical operations for their processing is excluded, the metal consumption of blanks is reduced, the production spaces required in this regard are reduced, the necessary labor supply is reduced, etc.OJSC “BELNIILIT” has successfully carried out experimental design and technological work on the new scientific and technical products creation, which are of great interest to the world manufacturers of piston rings. An industrial sample of a molding machine and a mold manipulator were manufactured.